Pathologic complete response and individual patient prognosis after neoadjuvant chemotherapy plus anti-human epidermal growth factor receptor 2 therapy of human epidermal gowth factor receptor 2-positive early breast cancer - Mackelenbergh, Marion Tina van; Loibl, Sibylle; Untch, Michael; Buyse, Marc; Geyer, Charles E.; Gianni, Luca; Schneeweiss, Andreas; Conte, Pierfranco; Piccart, Martine; Bonnefoi, Herve; Jackisch, Christian; Nekljudova, Valentina; et al. (Journal of clinical oncology, 2023)
PURPOSE - - The achievement of pathologic complete response (pCR) is strongly prognostic for event-free survival (EFS) and overall survival (OS) in patients with early breast cancer (EBC), and adapting postneoadjuvant therapy improves long-term outcomes for patients with HER2-positive disease not achieving pCR. We sought to investigate prognostic factors for EFS and OS among patients with and without pCR after neoadjuvant systemic treatment consisting of chemotherapy plus anti-HER2 therapy. - - MATERIALS AND METHODS - - We used individual data from 3,710 patients randomly assigned in 11 neoadjuvant trials for HER2-positive EBC with ≥100 patients enrolled, available data for pCR, EFS, and OS, and follow-up ≥3 years. We assessed baseline clinical tumor size (cT) and clinical nodal status (cN) as prognostic factors using stratified (by trial and treatment) Cox models separately for hormone receptor-positive versus hormone receptor-negative disease, and for patients who had pCR (pCR+; ypT0/is, ypN0) versus patients who did not achieve a pCR (pCR−). - - RESULTS - - The median follow-up overall was 61.2 months. In pCR+ patients, cT and cN were significant independent prognostic factors for EFS, whereas only cT was a significant predictor for OS. In pCR− patients, cT, cN, and hormone receptor status were significant independent predictors for both EFS and OS. Regardless of hormone receptor status, cT, and cN, the 5-year EFS/OS rates were higher in pCR+ patients than in pCR− patients. In most subsets with regards to hormone receptor and pCR status, cT and cN were independent prognostic factors for both EFS and OS, including pCR+ patients. - - CONCLUSION - - These results confirm that patients achieving pCR have far better survival outcomes than patients who do not. The traditional poor prognostic features, namely tumor size and nodal status, remain important even after a pCR.
Online veröffentlicht: 19. April 2023
Gesehen am 08.08.2023